PENGARUH SEROTONIN TERHADAP PERUBAHAN MOOD PADA REMAJA WANITA PREMENSTRUAL SYNDROME - Ruqaiyah, Ruqaiyah; Irwan, Hadriani; Alamsyah, Alamsyah; Harun, Ayatullah; Jannata, Rahma Winahyu; Amir, Fatmawati (Poltekkes Kemenkes Bandung, 2023)
A woman's regular monthly menstruation is positive indicator of health. However, majority of women have negative effects from symptoms arising during the second half of the menstrual cycle. This study aims to determine the effect of serotonin on mood changes in adolescent girls suffering from PMS and who don't. This research was conducted in April-July 2023 at Darul Arqam in Makassar. The research used a cross-sectional design with a sample size of 48 young women consisting of two groups, 24 groups with PMS and 24 without PMS, selected using purposive sampling. Mann-Whitney and Kruskall-Wallis analyses were used to examine the effect of serotonin on changes in mood and menstrual patterns in adolescent girls with and without PMS. The finding showed that there were differences in serotonin levels between groups of women who experienced PMS and those who did not experience PMS, with a value of p=0.012 p<α=0.05. The findings showed an influence of serotonin levels in the group of women who experienced PMS on mood changes (p = 0.001). In the group of women who did not experience PMS, serotonin levels did not influence mood changes (p = 0.875). Serotonin influences mood changes in women who experience PMS. However, serotonin does not have positive or negative effects on women who have not experienced PMS. There are differences in serotonin levels between women who experience PMS and those who don't. This study recommends to explore alternative treatment options for managing PMS symptoms that do not rely solely on serotonin regulation.